The Immune Adjuvant Effects of Flounder (Paralichthys olivaceus) Interleukin-6 on E. tarda Subunit Vaccine OmpV - Guo, Ming (Int J Mol Sci, 2017)
Interleukin-6 (IL-6) as a pleiotropic cytokine was widely used as an effective adjuvant for vaccines in mammals. In this study, the immune adjuvant effects of two forms of flounder (Paralichthys olivaceus) IL-6, including recombinant IL-6 (rIL-6) and pcDNA3.1-IL-6 (pcIL-6), were evaluated and comparatively analyzed on E. tarda subunit vaccine recombinant outer membrane protein V (rOmpV). The results showed that the relative percent survivals of flounder vaccinated with rOmpV plus rIL-6 or pcIL-6 were significantly higher than that in the two control groups, rOmpV plus recombinant 6× histidine-tag (rHis) or empty expression vector pcDNA3.1 (pcN3). The levels of specific serum antibodies and surface membrane immunoglobulin-positive (sIg+) lymphocytes in peripheral blood, spleen, and head kidney in the two adjuvant groups were also much higher than that in the two control groups. Compared with the two control groups, higher upregulated expressions of major histocompatibility complex class Iα (MHCIα), cluster of differentiation 8α (CD8α), MHCIIα, CD4-1, interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α) were detected in flounder vaccinated with rOmpV plus rIL-6 or pcIL-6 after challenge. In addition, the rOmpV plus rIL-6 could induce significant higher levels of specific serum antibodies, sIg+ lymphocytes and four genes expressions than rOmpV plus pcIL-6. These results demonstrated that both rIL-6 and pcIL-6 used as adjuvants could enhance the immune response and evoke immune protections against E. tarda infection, which has a significant value in controlling diseases using vaccines in flounder.